Defining neonatal sepsis. Issue 2 (April 2016) - Wynn, James L.
Abstract : Purpose of review: Although infection rates have modestly decreased in the neonatal intensive care unit (NICU) as a result of ongoing quality improvement measures, neonatal sepsis remains a frequent and devastating problem among hospitalized preterm neonates. Despite multiple attempts to address this unmet need, there have been minimal advances in clinical management, outcomes, and accuracy of diagnostic testing options over the last 3 decades. One strong contributor to a lack of medical progress is a variable case definition of disease. The inability to agree on a precise definition greatly reduces the likelihood of aligning findings from epidemiologists, clinicians, and researchers, which, in turn, severely hinders progress toward improving outcomes. Recent findings: Pediatric consensus definitions for sepsis are not accurate in term infants and are not appropriate for preterm infants. In contrast to the defined multistage criteria for other devastating diseases encountered in the NICU (e.g., bronchopulmonary dysplasia), there is significant variability in the criteria used by investigators to substantiate the diagnosis of neonatal sepsis. Summary: The lack of an accepted consensus definition for neonatal sepsis impedes our efforts toward improved diagnostic and prognostic options, and accurate outcomes information for this vulnerable population.